Day 1 Tue, September 30, 2014 2014
DOI: 10.2118/171656-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chemical Tracer Flowback in Unconventional Reservoirs

Abstract: Because of the need to quantify hydraulic fracture effectiveness, injection of chemical tracers in unconventional reservoirs has increased in popularity. Typical tracers are oil or water-soluble chemicals, which are injected into the formation along with the fracturing fluids. The tracers should invade a significant portion of the stimulated rock volume (SRV). The tracer backflow could shed light on the effectiveness of the hydraulic fracturing process and the SRV size. Emulsion tracers and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The existence of natural fractures is also supported by the general shape of the tracer return over time curves (Figure 2.12). A "smooth" tracer return curve generally implicates the existence of natural fractures according to Salman, et al (2014) (Figure 2.13). The tracer return curves from this study resembles those from the Bakken more so than the Eagle Ford.…”
Section: Communication V Injection Locationmentioning
confidence: 98%
“…The existence of natural fractures is also supported by the general shape of the tracer return over time curves (Figure 2.12). A "smooth" tracer return curve generally implicates the existence of natural fractures according to Salman, et al (2014) (Figure 2.13). The tracer return curves from this study resembles those from the Bakken more so than the Eagle Ford.…”
Section: Communication V Injection Locationmentioning
confidence: 98%
“…Seismic methods can detect fractures and faults but cannot detect whether fractures remain open . Chemical tracers are commonly used to measure pore volume, swept volume, and remaining oil saturation , and can also be used to assess fracture connectivity and stimulation. , The chemical tracer is injected into the reservoir together with the fracturing fluid. After the fracturing operation, the chemical tracer and the flowback fluid are collected together and their concentrations are analyzed.…”
Section: Coated Proppantmentioning
confidence: 99%
“…(3) During flow shut down, a downhole packer is introduced into the well to prop the next fracture (4) Opening the well (injector is being changed into a producer), the tracer can now be flown back with the fracturing fluid Salman et al [19] discussed the analysis of chemical tracers in flowback samples from unconventional reservoirs to determine the effectiveness of the treatment. They presented the flowback results for a multistage completion and concluded that tracer analysis can be used to assess the fractured system in the stimulated reservoir volume (highly fractured vs. sparsely fracture).…”
Section: Literature Reviewmentioning
confidence: 99%